Together We Learn: Students’ Perceptions of the Benefits of Group Work in Learning English - Deni Asrida; Nanda Dwi Aksari (Faculty of Education and Teacher Training of UIN Palopo, 2025)
Although group work is widely promoted in English as a Foreign Language (EFL) pedagogy, most studies have examined its benefits in isolation, focusing primarily on cognitive or affective aspects. Few scholarly studies have explored students’ perceptions holistically across cognitive, affective, and conative dimensions, particularly in Indonesian secondary school contexts where sociocultural norms influence classroom interaction. This qualitative study addresses that gap by examining how ninth-grade students at SMPN 2 Batusangkar perceive the role of group work in English learning. Thirteen students were purposively selected based on participation levels and teacher recommendations. Data from semi-structured interviews were analyzed using the Miles and Huberman framework. Findings indicate that group work enhances comprehension, accelerates task completion, and stimulates idea generation (cognitive); fosters enjoyment, self-confidence, and occasional frustration with passive peers (affective); and promotes activeness, responsibility, and collective problem-solving (conative). The study’s unique contribution lies in providing a culturally contextualized, multidimensional account of group work perceptions, offering actionable insights for designing structured, equitable, and engaging collaborative activities. These findings have key implications for EFL educators and curriculum developers seeking to balance learner autonomy with guided support to optimize participation, language development, and essential 21st-century skills.